Examining group facilitation in situ: the use of formulations in facilitation practice - Luis Alberto Franco; Mie F. Nielsen (2018)
In this paper we examine how the talk of the facilitator shapes group workshop interactions by using the conversational object 'formulation'. The data consist of video recordings of a corpus of four facilitated workshops held with management and development teams. By adopting an exploratory video-based investigation using conversational analysis to examine our data, we highlight the significance of three distinct set of formulations used by facilitators in workshops. Specifically, our findings show how formulations that encourage reflection or facilitate action, together with those collaboratively produced, enable sense making and the achievement of a temporal conversational order among participants. This research contributes to the study of facilitated workshops by offering a more nuanced approach to the understanding of the craftsmanship of doing facilitation, its effects on the workshop process and, ultimately, workshop outcomes.